2019
DOI: 10.1111/joim.12876
|View full text |Cite
|
Sign up to set email alerts
|

Innate and adaptive immune responses against human Puumala virus infection: immunopathogenesis and suggestions for novel treatment strategies for severe hantavirus‐associated syndromes

Abstract: Klingstr€ om J, Smed-S€ orensen A, Maleki KT, Sol a-Riera C, Ahlm C, Bj€ orkstr€ om NK, Ljunggren HG (Karolinska University Hospital, Stockholm, Sweden; Ume a University, Ume a, Sweden). Innate and adaptive immune responses against human Puumala virus infection: immunopathogenesis and suggestions for novel treatment strategies for severe hantavirus-associated syndromes (Key Symposium). J Intern Med 2019; 285: 510-523. latter conditions may also be applicable in severe hantavirus infections. Immune responses to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 115 publications
1
38
0
3
Order By: Relevance
“…This outcome may therefore also represent a universal rodent host response to orthohantaviruses. The absence of proinflammatory responses, correlating with asymptomatic infections in our non-reservoir host mouse model, strengthens the evidence that hantavirus disease is driven by inflammation [9,61]. Importantly, we observed no differences in viral load or tissue dissemination between WT and Mavs -/mice, indicating that other immune signaling pathways are involved in type I IFN production and viral control in vivo.…”
Section: Plos Pathogenssupporting
confidence: 85%
“…This outcome may therefore also represent a universal rodent host response to orthohantaviruses. The absence of proinflammatory responses, correlating with asymptomatic infections in our non-reservoir host mouse model, strengthens the evidence that hantavirus disease is driven by inflammation [9,61]. Importantly, we observed no differences in viral load or tissue dissemination between WT and Mavs -/mice, indicating that other immune signaling pathways are involved in type I IFN production and viral control in vivo.…”
Section: Plos Pathogenssupporting
confidence: 85%
“…At the same time, hantavirus infection triggers a massive activation of cytotoxic lymphocytes, which should serve to eradicate infected cells. However, despite high levels of activated NK cells and CD8 T cells in hantavirus-infected patients (Bjö rkströ m et al, 2011;Kilpatrick et al, 2004;Lindgren et al, 2011;Van Epps et al, 2002), analyses of autopsies from deceased patients have revealed that infected endothelial cells are intact (Zaki et al, 1995), and others have also reported not observing clear cytopathic effects on infected endothelial cells (Safronetz et al, 2014;Klingströ m et al, 2019;Vaheri et al, 2013). These observations suggested the possibility that hantaviruses could inhibit cytotoxic lymphocyte-mediated killing, likely contributing to the observed high levels of infected cells in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Well controlled human studies have shown that hantavirus infections cause aberrant activation of both innate and adaptive immunity (58). A potent antiviral IgG-response is associated with protection from severe disease during both HPS and HFRS (912) and passive transfer of serum antibodies could reduce case fatality rate in a small cohort of HPS patients (13).…”
Section: Introductionmentioning
confidence: 99%